Evaluation of the impact of HIV-1 infection and density of common nasopharyngeal bacterial colonizers in South African children immunized with 7-valent pneumococcal conjugate vaccine. Issue 7 (11th February 2020) - Olwagen, Courtney P.; Adrian, Peter V.; Madhi, Shabir A.
Abstract: Background: Due to limitations in standard culture methods, the impact of pneumococcal conjugate vaccine (PCV) immunization on nasopharyngeal bacterial carriage density is unclear, including among HIV-infected children. Methods: The prevalence and density of serotype/serogroup-specific pneumococcal and other nasopharyngeal colonizing bacteria were investigated in archived swabs of HIV-infected and HIV-uninfected, PCV-7 immunized (at 6, 10 and 14 weeks of age) South African children collected at 9 and 16 months of age. During the course of the study, PCV-immunization of children in Soweto was limited to study-participants, as the vaccine had not been introduced into the public immunization program. Results: At 9 months of age, the prevalence of overall pneumococcal colonization was lower in HIV-infected (58.6%) than HIV-uninfected children (69.9%, p =  0.02), mainly due to lower prevalence of non-vaccine-serotype colonization (27.8% vs. 40%, respectively; p =  0.047). The mean-log10 density of pneumococcal colonization was, however, higher in HIV-infected (4.81 CFU/ml) than HIV-uninfected pneumococcal colonized children (4.44 CFU/ml; p =  0.014); mainly due to higher mean-log10 density of PCV7-serotype colonization (4.21 vs. 3.72 CFU/ml; p =  0.014). No difference in the prevalence or density of overall pneumococci was found at 16 months of age. The prevalence of non-vaccine serotype colonization remained 1.7 fold higher in HIV-uninfected (60.4%) than HIV-infected children (50.9%, p =  0.049). Other differences included a lower prevalence of H. influenzae colonization in HIV-infected (42.3% and 56%) than HIV-uninfected children (64.2% and 73.4%) at both 9 and 16 months of age respectively; however, the density of colonization was similar. Conclusion: Increased carriage density of residual PCV7-serotypes might cause HIV-infected children to have a higher risk of pneumococcal disease. The higher carriage density observed in HIV-infected children could be attributed to a combination of factors, including HIV treatment and impaired host immunity. Additional studies are needed.